O PIENIACTWIE NA LITWIE WEDŁUG WŁODZIMIERZA GADONA - Godek, Sławomir (Zeszyty Prawnicze, 2016)
On Litigiousness in Lithuania according to Włodzimierz Gadon Summary Litigiousness is often mentioned in turn-of-the-18th- and 19th-century correspondence, memoirs and academic studies as a widespread abuse plaguing Lithuania. In 1818 an analysis of the causes of its prevalence was conducted in a short essay by Włodzimierz Gadon. Some of the causes he listed were inadequate land registration, a deficient statute of limitations, no mortgage law and no justices of the peace, professional pettifoggers, dishonest officials, poorly educated judges and the custom of landowners prosecuting runaway peasants years after their escape. The measures Gadon recommended against litigiousness were a land registration act, a uniform statute of limitations, the institution of a mortgage law and justices of the peace, and the prosecution of professional pettifoggers and dishonest officials.